Bone Marrow-Derived Mesenchymal Stem Cells Ameliorate Sepsis-Induced Acute Kidney Injury by Promoting Mitophagy of Renal Tubular Epithelial Cells via the SIRT1/Parkin Axis - Guo, Jun; Wang, Rong; Liu, Donghai (Frontiers in Endocrinology, 2021)
Sepsis is a common risk factor for acute kidney injury (AKI). Bone marrow-derived mesenchymal stem cells (BMSCs) bear multi-directional differentiation potential. This study explored the role of BMSCs in sepsis-induced AKI (SI-AKI). A rat model of SI-AKI was established through cecal ligation and perforation. The SI-AKI rats were injected with CM-DiL-labeled BMSCs, followed by evaluation of pathological injury of kidney tissues and kidney injury-related indicators and inflammatory factors. HK-2 cells were treated with lipopolysaccharide (LPS) to establish SI-SKI model in vitro. Levels of mitochondrial proteins, autophagy-related proteins, NLRP3 inflammasome-related protein, and expressions of Parkin and SIRT1 in renal tubular epithelial cells (RTECs) of kidney tissues and HK-2 cells were detected. The results showed that BMSCs could reach rat kidney tissues and alleviate pathological injury of SI-SKI rats. BMSCs inhibited inflammation and promoted mitophagy of RTECs and HK-2 cells in rats with SI-AKI. BMSCs upregulated expressions of Parkin and SIRT1 in HK-2 cells. Parkin silencing or SIRT1 inhibitor reversed the promoting effect of BMSCs on mitophagy. BMSCs inhibited apoptosis and pyroptosis of RTECs in kidney tissues by upregulating SIRT1/Parkin. In conclusion, BMSCs promoted mitophagy and inhibited apoptosis and pyroptosis of RTECs in kidney tissues by upregulating SIRT1/Parkin, thereby ameliorating SI-AKI.